Extracellular Matrix Markers for Disease Progression and Follow-Up of Therapies in Familial Amyloid Polyneuropathy V30M TTR-Related. Issue 1 (4th June 2013) - Cardoso, I.; Brito, M.; Saraiva, M.J.
Abstract : Familial Amyloidotic Polyneuropathy (FAP) is a disorder characterized by the extracellular deposition of fibrillar Transthyretin (TTR) amyloid, with a special involvement of the peripheral nerve. Several extracellular matrix proteins have been found elevated in tissues from FAP patients, namely metalloproteinase-9 (MMP-9), neutrophil gelatinase associated lipocalin (NGAL) and biglycan. In this work we assessed the levels of MMP-9, tissue inhibitor of metalloproteinase 1 (TIMP-1), NGAL, biglycan and chondroitin sulphate (CSPG) in an FAP V30M TTR-related transgenic mouse model at different stages of TTR deposition and after two different treatment approaches to remove fibrillar deposits. Immunohistochemistry or RT-PCR analysis showed that biglycan was already increased in animals presenting TTR deposited in a non-fibrillar state, whereas MMP-9, TIMP-1, NGAL and CSPG were elevated only in mice with TTR amyloid deposits. Mice treated with doxycycline, a TTR fibril disrupter, presented lower levels of MMP-9, TIMP-1 and NGAL, suggestive of matrix recovery. Mice immunized with TTR Y78F to remove TTR deposition showed significantly lower levels of all the five tested markers, suggesting removal of fibrillar and non-fibrillar deposits. Cellular studies using oligomeric TTR showed induction of MMP-9 when compared to soluble TTR, large aggregates or fibrils. Furthermore, this induction was neutralized by an anti-receptor for advanced glycation end products (RAGE) antibody, indicating RAGE engagement in this process. Further studies in a larger number of tissue samples will indicate the application of these ECM markers in parallel with Congo Red staining in tissue characterization of pre-clinical and clinical stages in FAP and other amyloidoses.